Seasonal Abundance of Aphids and Aphidophagous Insects in Pecan - Dutcher, James D. (Insects, 2012)
Seasonal occurrence of aphids and aphidophagous insects was monitored for six years (2006–2011) from full leaf expansion in May to leaf fall in October in “Desirable” variety pecan trees that were not treated with insecticides. Aphid outbreaks occurred two times per season, once in the spring and again in the late summer. Yellow pecan and blackmargined aphids exceeded the recommended treatment thresholds one time and black pecan aphids exceeded the recommended treatment levels three times over the six seasons. Increases in aphidophagous insect abundance coincided with aphid outbreaks in five of the six seasons. Among aphidophagous insects Harmonia axyridis and Olla v-nigrum were frequently collected in both the tree canopy and at the ground level, whereas, Coccinella septempunctata, Hippodamia convergens were rarely found in the tree canopy and commonly found at the ground level. Green lacewing abundance was higher in the ground level than in the tree canopy. Brown lacewings were more abundant in the tree canopy than at the ground level. Dolichopodid and syrphid fly abundance, at the ground level increased during peak aphid abundance in the tree canopy. Application of an aqueous solution of fermenting molasses to the pecan foliage during an aphid outbreak significantly increased the abundance of ladybeetles and lacewings and significantly reduced the abundance of yellow pecan, blackmargined and black pecan aphids.